Deleuze and Marx - Jain, Dhruv (Deleuze Studies, 2009)
Writings on Deleuze and Guattari's twin volumes, Capitalism and Schizophrenia, have often focused on questions about desire, body without organs, the schizophrenic etc. There have been a few notable exceptions that have attempted to articulate and expound upon the numerous political problems that Deleuze and Guattari attempt to resolve through analyses of concepts such as de-/re-territorialization, coding and re-coding etc, however a specter is haunting Deleuze and Guattari that has yet to be explained, articulated and debated; the specter of Karl Marx. This volume attempts to analyze the relationship between Deleuze (and Guattari) and Marx and their respective works. This volume is an intervention into the fields of Deleuze Studies, Marxist and Marxian philosophy and political economy, and critiques of capitalism through an examination of the relationship between Deleuze and Marx. Themes that will be covered in this volume include hegemony and theories of imperialism, the role of philosophy in changing the world, surplus, tensions between the virtual and the potential, ideology and noology, modes of production, and the very nature of anti-capitalist politics in Deleuze's work. This volume will be of interest to people interested in Deleuze Studies who are interested in questions of politics and critiques of capitalism, Marxist theory and philosophy and people interested in political economy.Key Featuresoffers new perspectives on Deleuze's early workilluminates new connections between Deleuze's and Marx's workincludes a critical re-reading of Deleuze's workforegrounds a critique of Capitalism in Deleuze's workContributors include: Bruno Bosteels, Alberto Toscano, Jason Read, Jeremy Gilbert Simon Choat and Aidan Tynan